ISLAMIC FINANCE IN SUSTAINABLE ECONOMY: EMPOWERMENT OF SUKUK WAKALAH TO BUILD WASTE INDUSTRY - Muhammad Zaid Farhand; Putri Leli Nurjanah; Muhammad Nurcholis (Airlangga International Journal of Islamic Economics and Finance, 2020)
The challenge that Indonesia faces in processing natural and non-biological natural resources is the problem of waste management. High population figures, as well as increased incomes, affect consumption patterns that lead to increased waste generation in Indonesia. It is projected that in 2030 - 2050 waste production will increase, the problem of waste management in Indonesia can be seen from the following indicators, namely the high amount of waste generated, the level of waste management services is still low, limited number of final landfills, waste management institutions and cost problem. To overcome this problem, the issuance of wakalah sukuk as a source of funding for the waste industry center is a solution that can be done by the government. This research uses descriptive analysis research methodology with literature study data collection techniques. In the discussion explained about the concept of sustainable economy and wakalah state sukuk scheme in providing technology procurement financing to the waste processing industry. This research concluded that the wakalah state sukuk could be an alternative financing for technology procurement for the waste industry in increasing the effectiveness and efficiency of the company so that it is more environmentally sound and appropriate with SDG's.